Pesantren In Social Construction Perspective (The Educational Orientation Of The Sidogiri Pesantren) - Try Heni Aprilia; Agus Harisuddin Masrof; Anis Humaidi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Pesantren has been considered a model of educational institution that has advantages both from the aspect of scientific tradition and the internalization of the morality of Muslims. Pesantren are very good at dialectical with conflicting cultural theses and give birth to a synthesis of new social constructions. Pesantren is also the most creative and innovative social institution. Because of its philosophy: al-muhafadhu 'alal qadimis sholeh wal akhdu bil Jadidil Ashlah. The purpose of this study is to find out the general description of the orientation of education in the Sidogiri Pesantren with the various challenges of social change that occur in society. This research is important because it tries to reveal how the Sidogiri Pesantren carries out its roles to the expectations and needs of the community who require services from the Sidogiri Pesantren related to religious services, education, and other social roles. By using a case study at the Sidogiri Pesantren, data was collected through a documentation study by tracking related literature sources, documents or archives, and observations. Among the findings are: 1) The change in the form of the education unit managed by the Sidogiri pesantren is essentially a change from the non-formal education system to the formal education system, in the form of madrasah education units. However, the Sidogiri Pesantren still maintains its salafiyah education system; 2) The Pesantren is always innovating and adapting; 3) The independence of the Sidogiri Pesantren in the economic field is very beneficial for both the students.